Rooted in place: equitable placemaking as green stormwater infrastructure - Huerta, Esteban (Kansas State University, 2021)
Today historically marginalized neighborhoods are among the most vulnerable communities to changes in their environment and socioeconomic status. This often results in the displacement of the community members or loss of community assets. This report aims to build resiliency to the threat of stormwater runoff while creating inclusive spaces for existing residents through green stormwater infrastructure and equitable placemaking. This study focuses on vulnerable communities in one of the historically redlined neighborhoods adjacent to Brush Creek in Kansas City, MO, as a case study to examine the development of green infrastructure that protects against urban flooding while bolstering local economies and sense of place.
Keywords: Green infrastructure; Social equity; Ivanhoe; Placemaking